2018
DOI: 10.5114/aoms.2017.67675
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of esophagogastroduodenoscopy in children with chronic abdominal pain

Abstract: IntroductionChronic abdominal pain (CAP) is one of the most common indications of esophagogastroduodenoscopy (EGD) in the pediatric population. However, there is not enough information about the diagnostic yield of EGD in children with CAP. We aimed to evaluate the diagnostic yield of EGD in children with CAP in the Eastern Black Sea region of Turkey.Material and methodsThe study included children (n = 372) who underwent EGD for the primary indication of chronic abdominal pain during an 18-month period. We col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 36 publications
3
20
1
2
Order By: Relevance
“…Other investigators have demonstrated high diagnostic yield when EGD was performed for these indications, especially in the presence of alarm symptoms; however, these studies considered mild nonspecific inflammation in the esophagus, stomach, and duodenum to be a positive result. 5,13 These data were consistent with our findings; however, we discovered that, in the absence of H pylori infection, celiac disease, or other rare findings, the presence of mild upper gastrointestinal inflammation did not significantly change clinical management in study participants who were already taking a H2-blocker or a PPI. Our patients who were already on an H2-blocker or PPI were slightly more likely to require a change in clinical management after EGD (9.2% vs 6.0%), but this difference was not statistically significant (P = .3239).…”
Section: Discussionsupporting
confidence: 90%
“…Other investigators have demonstrated high diagnostic yield when EGD was performed for these indications, especially in the presence of alarm symptoms; however, these studies considered mild nonspecific inflammation in the esophagus, stomach, and duodenum to be a positive result. 5,13 These data were consistent with our findings; however, we discovered that, in the absence of H pylori infection, celiac disease, or other rare findings, the presence of mild upper gastrointestinal inflammation did not significantly change clinical management in study participants who were already taking a H2-blocker or a PPI. Our patients who were already on an H2-blocker or PPI were slightly more likely to require a change in clinical management after EGD (9.2% vs 6.0%), but this difference was not statistically significant (P = .3239).…”
Section: Discussionsupporting
confidence: 90%
“…For example, cytokines such as IL-1β, IL-1ra, and IL-6 used for the clinical approach to ulcerative colitis relapse can be investigated in AA and AML [12,23,24]. Colonoscopy may be used for higher diagnostic reliability of AML in children as in a recent study in which esophagogastroduodenoscopy was performed in children with chronic abdominal pain [25]. Thus, in an acute stage of AML, colonoscopy may detect the intestinal changes which could be associated with AML by the same logical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Sheiko et al [9] identified endoscopic abnormalities in 28.9% and histopathological abnormalities in 35.2%. Akbulut et al [10]reported a high diagnostic yield of 56.2% but concluded that a significantly greater diagnostic yield of EGD was present in patients with chronic abdominal pain and alarm symptoms (65.1%) compared to those without symptoms (45.2%). Dahshan et al [11]and Puzanovova et al [12]highlighted the importance of a routine biopsy during the approach of chronic abdominal pain.…”
Section: Discussionmentioning
confidence: 99%